ENGINEERING STUDENTS’ PERCEPTIONS OF SUSTAINABILITY IN THE REHABILITATION OF BUILDINGS: A CASE STUDY - Coimbra, José (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this case study is to analyse the perceptions and knowledge of university students, regarding the implementation of proper practices, towards a high level of sustainability of rehabilitated buildings. During 2016-17, a group of twenty-one students attended “Pathologies and Rehabilitation of Buildings”, a third-year subject of a Portuguese Civil Engineering course, which aims to deepen the knowledge that will allow students to use sustainable practices in old buildings in need of rehabilitation. Qualitative and quantitative data was collected from observation and analysis of the rehabilitation process of a building located in the city of Porto, Portugal, as well as from the analysis of a questionnaire about how this practical activity has enriched students´ technical experience. The results indicate students’ increasing awareness regarding the importance of practical knowledge about building rehabilitation, using sustainability criteria to transform highly deteriorated buildings into spaces whose dwellers can achieve an easier integration at the environmental, social and economic levels. Nevertheless, it should be noted that only a few students reveal deeper knowledge of the building pathologies, of which the most common are humidity infiltrations and the lack of thermal insulation. The results of the case study will be used to improve teaching practice in this university course and to increase students´ practical application of sustainable rehabilitation concepts to the built environment. In this way, the establishment of the effectiveness of an active pedagogy, in order to prepare future engineers, capable of leading a building rehabilitation sustainable process, was a driving factor in this study.